Finishing properties of two selected types of coating materials on sepetir wood / Fathin Shahirah Mohd Hamidi - Mohd Hamidi, Fathin Shahirah (Faculty of Applied Sciences, 2015)
Finishing is the one of the processes that has a great importance for technical, economical and aesthetical evaluation of the wood materials. Wood surfaces that coated with coating materials can be protected from certain adverse situations such as moisture, changes in dimensions and deterioration by microorganisms and fungi. In this study, it was conducted to determine finishing properties of different types of coating materials and methods of application on Sepetir wood (Sindora spp.). The timber is suitable for general planking, light construction, ceiling, packing cases and pallets. The streaked material is, however, highly prized as a superior cabinet wood and is suitable for decoration works like joinery and paneling. There are two types of coating materials and two different methods of application used in this study. The total samples of Sepetir wood are 48 and there are different measurements for each types of testing. Three types of testing and two different types of standards were used in this study to determine the strength of the coating materials towards Sepetir wood. There are slightly differences on the results of testing from both coating materials and methods of application. However, the timber is moderately durable and is very difficult to treat with preservatives.